How does the Risk Attitude affect the Bidding Behavior of Farmers? Results of an Experimental Auction - Gesa Sophie Holst; Oliver Musshoff; Elisabeth Vollmer (German Journal of Agricultural Economics (GJAE), 2018)
Auctioning off goods is a widespread practice in the agricultural sector. The revenue equivalence theorem predicts that independent of the type of auction, the revenues are identical under fulfillment of specific conditions. One of these conditions is that bidders must be risk neutral; this condition, however, often fails in reality. An experiment was carried out with farmers to investigate how the bid amount is influenced by the individual risk attitude. In the experiment, farmers were able to buy a good with a private value in four different auctions types. Results indicate that the revenues in auctions are affected by the risk attitude of the bidders. Moreover, the influence of the risk attitude depends on the auction type.
Keywords: 330